Konsep Pendidikan Islam Perspektif Al-Qabisi - Mawaddah; Agus Rahman Waruwu; zizah Hanum OK (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
This research aims to examine Al-Qabisi's significant contribution to Islamic education through an in-depth analysis of his famous work, "Ahkam al-Muta'allimin". Al-Qabisi, a 10th-century scholar and educational thinker, offers rich insights into teaching methodology, teacher ethics, and the rights and obligations of students. Through qualitative research methods with a historical-philosophical approach, this research reveals the educational principles proposed by Al-Qabisi and their relevance in the context of contemporary Islamic education. The results of the study show that Al-Qabisi emphasizes the importance of morality and ethics in education, both for teachers and student. He also highlighted interactive and adaptive teaching methods according to students' needs and abilities. These principles, although developed in a medieval context, still have strong relevance in curriculum development and teaching methods in the modern era. This research concludes that Al-Qabisi's educational thought not only contributes to the history of Islamic education, but also offers views that can be applied in an effort to improve the current Islamic education system. Thus, Al-Qabisi's thoughts can become the basis for developing a more holistic and inclusive educational approach in the modern Islamic world.